Terapi Musik Klasik terhadap Perubahan Gejala Perilaku Agresif Pasien Skizofrenia - I Wayan Candra; I Ketut Gama (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2014)
This research aims at the influence of classical music therapy to changes in behavioral symptoms in patients skizofrenia aggressive. This is the type of pre-experimental by using the One-group pre-test-posttest design. Sampling tekhnique bys consecutive sampling.The sample is 15 peoples. Type of data is primary data through observation. The results aggressive behavior of schizofenia patients before therapy is given most of the music that is as many as 11 people (73.3%) in the moderate category. Aggressive behavior of schizofrenia patients after therapy is given most of the music that is as many as 12 people (80%) in the mild category statistical result obtained Wilcoxon Sign Rank test,p=0.000p 0.010, meaning there is a very significant influence classical music therapy to change symptoms of aggressive behavior in patients skizofrenia in space Kunti RSJ Bali Province in 2013.